Numerical simulations to the nonlinear model of interpersonal Relationships with time fractional derivative - Gencoglu, Muharrem Tuncay; Baskonus, Haci Mehmet; Bulut, Hasan (Amer Inst Physics, 2017)
The main aim of this manuscript is to obtain numerical solutions for the nonlinear model of interpersonal relationships with time fractional derivative. The variational iteration method is theoretically implemented and numerically conducted only to yield the desired solutions. Numerical simulations of desired solutions are plotted by using Wolfram Mathematica 9.
11th International Conference on Mathematical Problems in Engineering, Aerospace and Sciences (ICNPAA) -- JUL 04-08, 2016 -- Univ La Rochelle, La Rochelle, FRANCE
Keywords: Variational Iteration Method; Differential-Equations; Dynamics; Chaos